Association of Age With Lower Urinary Tract Function in Adult Men Presenting for Urodynamics: A Database Analysis - Sanjay Sinha (Société Internationale d’Urologie Journal, 2021)
Background: Knowledge regarding lower urinary tract function in adult men could help in making informed choices. Few studies have examined the entire spectrum of adult males. Methods: This is a retrospective analysis of all adult men with refractory non-neurogenic urinary symptoms presenting to a tertiary center over 9 years. International Continence Society defined indices bladder outlet obstruction index (BOOI) and bladder contractility index (BCI) were calculated with established classification. Storage abnormality was defined as presence of detrusor overactivity, poor compliance (< 20mL per cm H20) or both. Data were analyzed by non-parametric tests using SPSS (version 20.0.0, Armonk NY ) (P < 0.05 significant; 2-tailed). Where appropriate, correction for multiple hypothesis testing was applied. Results: A total of 1596 men (range 18 to 91 years, median 51.0 years; IQR 34 to 64 years) were eligible. Median BCI and BOOI were 99.5 and 37.0, respectively, and a storage abnormality was noted in 41.7%. On multivariate analysis, age was significantly associated with urodynamic findings. While not strictly linear, for each 10 years increase in age, on average, the BCI fell 2.4 points and the BOOI increased by 2.4 points. Increasing age was also associated with increasing odds of finding a storage abnormality (OR 1.015; 95%CI 1.008 to 1.022; P < 0.001). On post hoc analysis (Bonferroni correction), men under 30 years were least likely of any group to show obstruction (30.3%; median BOOI 26). Conclusions: Adult men with refractory urinary symptoms show age-associated differences in urodynamic findings. An awareness of these trends can help take more informed decisions in clinical care.